2018
DOI: 10.1016/j.bprint.2018.e00028
|View full text |Cite
|
Sign up to set email alerts
|

3D bioprinted biomask for facial skin reconstruction

Abstract: Skin injury to the face remains one of the greatest challenges in wound care due to the varied contours and complex movement of the face. Current treatment strategies for extensive facial burns are limited to the use of autografts, allografts, and skin substitutes, and these often result in scarring, infection, and graft failure. Development of an effective treatment modality will greatly improve the quality of life and social integration of the affected individuals. In this proof of concept study, we develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 17 publications
(17 reference statements)
0
41
0
Order By: Relevance
“…Indeed, keratinocytes instruct fibroblasts to produce several tissue-forming factors, i.e., keratinocyte growth factor (KGF), fibroblast growth factor (FGF), IL-6, GM-CSF, hepatocyte growth factor (HGF), IL-6, IL-19, and PDGF-BB [ 64 , 65 ]. Nonetheless, merely eleven of the reviewed articles introduced fibroblasts and keratinocytes together in their models [ 22 , 23 , 24 , 31 , 32 , 66 ], and more importantly, only five of these works have successfully created vascularized, full-thickness skin substitutes [ 3 , 4 , 7 , 20 , 26 ].…”
Section: Overview Of Current Research On Extrusion-based Skin Biopmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, keratinocytes instruct fibroblasts to produce several tissue-forming factors, i.e., keratinocyte growth factor (KGF), fibroblast growth factor (FGF), IL-6, GM-CSF, hepatocyte growth factor (HGF), IL-6, IL-19, and PDGF-BB [ 64 , 65 ]. Nonetheless, merely eleven of the reviewed articles introduced fibroblasts and keratinocytes together in their models [ 22 , 23 , 24 , 31 , 32 , 66 ], and more importantly, only five of these works have successfully created vascularized, full-thickness skin substitutes [ 3 , 4 , 7 , 20 , 26 ].…”
Section: Overview Of Current Research On Extrusion-based Skin Biopmentioning
confidence: 99%
“…Indeed, PRP supplies cells with the appropriate stimuli for the proliferation, migration, and ECM protein synthesis. PRP or merely fibrinogen has been used in bioink formulations as a single-component bioink [ 24 ] or mixed with other molecules, including but not limited to collagen [ 21 , 22 , 66 ], dECM [ 7 ], alginate [ 30 ], gelatin [ 20 , 23 , 43 ], and others [ 4 ].…”
Section: Cell-laden Bioinksmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, three-dimensional (3D) bioprinting has been introduced in the area of wound repair or healing—in particular, for the treatment of large wounds [13]—because of its capability of constructing complex micro-architectures with cellular components [14,15,16,17] and patient-specific features, such as matching wound dimensions and the use of patient-originated cells, which avoid immune rejection [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…HA is the main component of the epidermis and dermis in the skin and is an excellent moisturizer [25]. Studies have also shown that HA interacts with endothelial cell receptors (CD44) to increase cell proliferation and promote angiogenesis, enhance collagen deposition and increase re-epithelialization in skin regeneration [13,21,22,23,24,25,26]. Additionally, HA is rapidly turned over in the body by hyaluronidase, with half-lives ranging from hours to days.…”
Section: Introductionmentioning
confidence: 99%